The Central Provinces Land Revenue Act, 1917 (II of 1917) - Government of the Central Provinces (Government of the Central Provinces, 1947)
The Central Provinces Land Revenue Act, 1917, along with its subsequent amendments, establishes a comprehensive framework for land revenue administration, land tenure, and dispute resolution in the Central Provinces. It defines the roles and powers of revenue officers, including Tahsildars and Settlement Officers, while outlining procedures for revenue collection, land settlement, and maintenance of records. The Act protects the rights of landowners, leaseholders (thekadars), and village officials, providing clear mechanisms for appeals, ejectment, and succession of land rights. Amendments introduced between 1948-1951 enhanced provisions for assessment revisions, crop failure relief, and boundary management. Overall, the Act balances the interests of the state and landholders, ensuring structured governance, agricultural productivity, and tenure security.
Government of the Central Provinces and Berar
Keywords: Land Revenue; Central Provinces; Revenue Officers; Landowners’ Rights; Settlement Procedures; Thekadars; Tahsildars; Ejectment; Record-Keeping; Amendments